Understanding IoT Adoption in Botswana’s SMEs: A Research Onion Approach - Mphale, Ofaletse; Gorejena, Karikoga Norman; Nojila, Olebogeng Hellen (Journal of Information System and Informatics, 2024)
The advent of the Internet of Things (IoT) presents a transformative opportunity for Small and Medium-sized Enterprises (SMEs), unlocking their potential for enhanced operational efficiency, productivity, and data-driven decision-making. However, harnessing these benefits necessitates a rigorous and structured methodological approach. On the next hand, selecting an appropriate research methodology can be problematic, as it demands consideration of context-specific factors. This study addresses a significant gap by theoretically evaluating and proposing a suitable "research onion" methodological approach, which can be employed to explain IoT adoption in Botswana's SMEs. This structured approach provides a comprehensive analytical lens comprising the research philosophies, research strategy, approaches, choices, time horizons, techniques and procedures. By carefully applying and justifying each element within the research onion’s distinct layers, the study empowers Information Systems (IS) researchers to effectively explain their methodological decisions. Hence, findings will inform policymakers and decision-makers in Botswana, enabling them to design targeted interventions that promote widespread IoT adoption in SMEs. Future research will empirically test this framework in Botswana's SME sector using surveys, thus furthering our understanding of the IoT adoption factors in SMEs.